The effect of aged garlic extract on blood pressure and other cardiovascular risk factors in uncontrolled hypertensives: the AGE at Heart trial - Ried K; Travica N; Sali A (Dove Medical Press, 2016)
Karin Ried,1–3 Nikolaj Travica,1 Avni Sali1 1National Institute of Integrative Medicine, Melbourne, 2Faculty of Health Science and Medicine, Bond University, Gold Coast, 3Department of General Practice, University of Adelaide, Adelaide, Australia Background: Hypertension affects 30% of adults worldwide. Garlic supplements have shown promise in the treatment of uncontrolled hypertension, and the mechanism of action is biologically plausible. Our trial is the first to assess the effect of aged garlic extract on central blood pressure and arterial stiffness, regarded as important risk factors for cardiovascular morbidity. Subjects and methods: A total of 88 general practice patients and community members with uncontrolled hypertension completed a double-blind randomized placebo-controlled trial of 12 weeks investigating the effect of daily intake of aged garlic extract (1.2 g containing 1.2 mg S-allylcysteine) or placebo on blood pressure, and secondary outcome measures of central-hemodynamics and other cardiovascular markers, including cholesterol, homocysteine, platelet function, and inflammatory markers. Results: Mean blood pressure was significantly reduced by 5.0±2.1 mmHg (P=0.016) systolic, and in responders by 11.5±1.9 mmHg systolic and 6.3±1.1 mmHg diastolic compared to placebo (P<0.001). Central hemodynamic-measures tended to improve in the garlic group more than in the placebo group, including central blood pressure, central pulse pressure, mean arterial pressure, augmentation pressure, pulse-wave velocity, and arterial stiffness. While changes in other cardiovascular markers did not reach significance due to small numbers in subgroups with elevated levels, trends in beneficial effects of garlic on the inflammatory markers TNFα, total cholesterol, low-density lipid cholesterol, and apolipoproteins were observed. Aged garlic extract was highly tolerable and acceptable, and did not increase the risk of bleeding in patients on blood-thinning medication. Conclusion: Our trial suggests that aged garlic extract is effective in reducing peripheral and central blood pressure in a large proportion of patients with uncontrolled hypertension, and has the potential to improve arterial stiffness, inflammation, and other cardiovascular markers in patients with elevated levels. Aged garlic extract was highly tolerable with a high safety profile as a stand-alone or adjunctive antihypertensive treatment. Keywords: hypertension, central blood pressure, arterial stiffness, cardiovascular risk factors, aged garlic extract